Results on Fro?lich's Brain wave model - Ucar, A.; Hyland, G.J. (University of Split, 2000)
The study of a mathematical model, i.e. Fröhlich's Brain-wave model, pertinent to the propagation of brain waves into the Great Membrane, is the focus of interest in this paper: Some new results are presented concerning the response of the system to external stimuli - both ac and dc. In contrast to an earlier claim that a restricted version of the model (containing only 2 degrees of freedom) exhibits a chaos only when the external stimulus contains both ac and dc components we find that ac component alone is sufficient. The extensive bifurcation diagrams of the model are given and the detail of chaotic region is clearly presented for this case.
Keywords: Deterministic Chaos; Electroencephalogram; External Stimuli; Frölich's Brain-Wave Model